PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR SISWA MATERI ORGANISASI SDN 040517 TIGA JUMPA - Susanti, Dewi Afriany; Eduard, Eduard; Karo, Karmila Br (Jurnal Curere, 2024)
This research aims to determine the effect of using the Numbered Head Together Cooperative learning model on students' learning of Organizational material in class V of SD Negeri 040517 Three Meetings. This type of research is Quasi Experimental research with the research instrument being a multiple choice test with 10 questions. Based on the calculation results, the average of the students' final tests was 77.93 in the experimental class and the average in the control class was 70. The frequency table of the final test scores in the experimental and control classes was distributed in absolute frequency and relative frequency tables and then connected in the form of a histogram to find out student learning outcomes after learning using the Numbered Head Toger (NHT) learning model in the experimental class and conventional control class. From the statistical test result, the calculed t-value 2,263 was found tobe greater than tabulator t-value 0,127 with a significance level of 0.05 which states that Ha is accepted and Ho is rejected, it can be concluded that the use of the Numbered Head Togerher (NHT) model has a significant effect on student results on organizational material in class V Negeri 0 40517 Three see you.Keywords: Learning Outcomes, Numbered Head Toger (NHT) Model